(untitled) (Ukrainian Journal of Ophthalmology, 2024)
Purpose. This study was conducted to compare the improvement in visual acuity and contrast sensitivity before and after neodymium yttrium aluminum garnet (Nd-YAG) capsulotomy in patients with posterior capsular opacity. Materials and Methods. A prospective study of 72 eyes of 60 patients with posterior capsular opacity (PCO) was conducted in the Department of Ophthalmology after approval from the institutional ethical committee of M S Ramaiah Medical college. A complete ophthalmological examination, including a detailed history, best corrected visual acuity using Snellens chart, and contrast sensitivity (before and after Nd- YAG capsulotomy) using Pelli Robson chart, slit lamp examination, IOP measurement, and fundus examination were performed after obtaining informed consent adherence to the tenets of Declaration of Helkinski . Results. The study comprised 60 patients, age groups ranging from 50 to 96 years, with the mean age of patients in our study being 65.943±8.83 years. BCVA of 62 eyes (86.2%) was between 6/18 and 6/60. After Nd YAG capsulotomy, patients showed great improvement in vision, with 63 eyes (87.5%) having improved BCVA of better than 6/12, and 24 eyes (33.3%) showing BCVA of 6/6 (p < 0.001). The contrast sensitivity of 69 eyes (95.83% ) was between 0 and 1.65 log units, followed by 3 eyes(4.17%) between 1.80 and 1.95 log units. After Nd-YAG capsulotomy, contrast sensitivity of 61 eyes (84.72%) improved to 1.80 – 2.25 log units, whereas the remaining 11 eyes (15.28%) showed contrast sensitivity of 1.20 – 1.65 log units (p < 0.001) Conclusion. Nd-YAG capsulotomy is an effective and relatively safe procedure for the management of posterior capsular opacity. It significantly improves both visual acuity and contrast sensitivity, thereby improving the quality of vision.